The Struggle of a Prostitution Girl in Kishwar Naheed’s Poetry, We Sinful Women: Feminism Issues - Martina Girsang; Rinny Sherina Putri Sianturi; Yance Cerelina Sihotang; Nelly Kristin; Arta Jelita Sitohang (Lembaga Jurnal dan Publikasi Universitas Muhammadiyah Buton, 2023)
In this research, the researcher decides to analyze feminism in Kishwar Naheed’s selected poems which have the same theme of caste inequality between women and men. This research method makes use of qualitative data analysis. Qualitative research looks for reasons and explanations rather than simply describing the research method and summarizing its findings. James (1998:576) says that feminism is based on the idea that women are disadvantaged or oppressed compared to men and that their oppression is in some way illegitimate or unjustified. Kishwar Naheed disagrees with the idea that all women are sinful and are viewed as objects and properties that can be abused by man-made laws of intensity and equity. According to some interpretations, the poem